Deutschförderung am Arbeitsplatz: Vorgesetzten-Schulung und Lernstatt Deutsch - Maurer, Ernst; Stotz, Daniel (My University, 2004)
A set of further education workshops is described and analysed which aim to promote the communicative competence in German of foreign-language workers employed by the city of Zurich. The workshops were complemented with seminars for the employees' superiors, enabling them toenhance the language-learning potential of the workplace. The workshops did not only aim at language competence, but also at the workers' self-esteem and equality of the sexes. A qualitative evaluation study has delivered the finding that the desired outcomes have been achieved mainly as a result of the coupling of the superiors' and the employees' workshops, and because the latter were firmly oriented towards the workplace. A "Language Portfolio for People in Migration" could further enhance the development of action-oriented language competence.